Versatility of the adenovirus-vectored foot-and-mouth disease vaccine platform across multiple foot-and-mouth disease virus serotypes and topotypes using a vaccine dose representative of the AdtA24 conditionally licensed vaccine. Issue 48 (19th November 2018) - Barrera, José; Brake, David A.; Schutta, Christopher; Ettyreddy, Damodar; Kamicker, Barbara J.; Rasmussen, Max V.; Bravo de Rueda, Carla; Zurita, Mariceny; Pisano, Melia; Hurtle, William; Brough, Douglas E.; Butman, Bryan T.; et al.
Highlights: The AdtFMD vaccine platform is versatile for multiple FMDV serotypes and topotypes. Cattle were immunized with one of 16 different AdtFMD monovalent vaccines. All AdtFMD monovalent vaccines elicited FMDV neutralizing antibodies in cattle. All AdtFMD monovalent vaccines protected cattle against homologous FMDV challenge. Cattle studies were conducted using a commercially viable AdtFMD vaccine dose. Abstract: We investigated the serotype- and topotype versatility of a replication-deficient human adenovirus serotype 5 vectored foot-and-mouth disease (FMD) vaccine platform (AdtFMD). Sixteen AdtFMD recombinant subunit monovalent vaccines targeting twelve distinct FMD virus (FMDV) serotype/topotypes in FMD Regional Pools I-VII were constructed. The AdtA24 serotype conditionally licensed vaccine served as the basis for vaccine design and target dose for cattle clinical trials. Several vaccines contained an additional RGD motif genetic insertion in the adenovector fiber knob, and/or a full-length 2B gene insertion in the FMDV P1 gene cassette. In 13 of the 22 efficacy studies conducted, naïve control and AdtFMD vaccinated cattle were challenged intradermolingually at 2 weeks post-vaccination using a FMDV strain homologous to the AdtFMD vaccine strain. Each of the 16 AdtFMD vaccines were immunogenic based on the presence of homologous neutralizing antibodies in the serum of approximately 90% of total vaccinates (n = 375) on the day of challenge. Importantly, for 75% of vaccines tested, the effective dose that conferred 100% protection against clinical FMD was identical to or in some cases lower than, the minimum protective dose for the conditionally licensed AdtA24 vaccine formulated with ENABL® adjuvant. Results also confirmed the capability of the AdtFMD vaccine platform to differentiate infected from vaccinated animals (DIVA) across the five FMDV serotypes evaluated. Collectively, this comprehensive set of FMD cattle vaccine dose ranging studies highlights the serotype- and topotype versatility of the AdtFMD vaccine platform for further development, licensure, and application in FMD outbreak control and disease eradication efforts.